Layer-fMRI acquisition and analysis - Marsh, Daniel C. (2023)
Functional Magnetic Resonance Imaging (fMRI) is a widely adopted imaging modality used to study human brain function. The advancements in MR hardware and acquisition have enabled researchers to investigate brain function at sub-millimetre resolution, detecting brain activation at depths across the cortex. Layer-fMRI at ultra-high field (UHF, defined as B0 ≥ 7 T) has the potential to answer many neuroscience questions that were previously untenable due to low spatial resolution or a low signalto-noise ratio (SNR). In addition, the combination of layer-fMRI with electroencephalography (EEG) provides a tool to investigate neuronal oscillation across cortical depths.